In Silico Evaluation of Drug-Likeness, ADMET Profile, and Toxicity of Antimalarial Compounds from the Bark of Alstonia scholaris - Zakki Aqimul Haq, Mohammad; Fahriza, M. Raffi; Taufan Insani, Gilang; Putra Rahmatullah, M. Fauzan; Waluyo, Seagames; Tias Pratama, Anggi; Bahiyah Abd Wahid, Nurul; Rahmatika Primandiri, Poppy; Santoso, Agus Muji (Jurnal Biodjati, 2026)
Malaria remains a major global health problem, particularly in tropical countries, highlighting the need for new antimalarial agents with favorable pharmacokinetic and safety profiles. This study aimed to evaluate the drug-likeness, ADMET properties, and toxicity of six bioactive compounds derived from Alstonia scholaris bark using an in silico approach. Computational analyses were performed using SwissADME, pkCSM, AdmetSAR, and ProTox-3.0 to assess absorption, distribution, metabolism, excretion, and toxicity parameters, as well as Lipinski’s Rule of Five. The results showed that four compounds met all Lipinski criteria, while two exhibited logP values greater than 5, suggesting potential limitations in lipophilicity. Predicted VDss values suggested moderate and variable systemic distribution, and none of the compounds were predicted to interact with CYP2D6. Toxicity analysis indicated generally low toxicity, with α-Amyrin classified as non-toxic (LD₅₀ = 70,000 mg/kg; toxicity class VI). Among the compounds, Spirost-8-en-11-one demonstrated the most favorable pharmacokinetic profile, with high gastrointestinal absorption and the highest total clearance. In conclusion, the evaluated compounds exhibit promising pharmacokinetic and safety profiles as potential antimalarial candidates. These findings provide preliminary computational evidence supporting further in vitro and in vivo validation to confirm their efficacy and safety.